Nursing care for the transgender population in primary health care: an integrative review - Carneiro Chagas, Manoella Alves; dos Santos, Adriano Maia; Neves de Jesus, Naila (Investigación y Educación en Enfermería, 2023)
Objective. To describe the care provided to the transgender population by nursing in Primary Health Care (PHC). Methods. Integrative literature review performed in the Virtual Health Library (VHL), Medline/PubMed and Web of Science (WoS) databases without a pre-established time frame, using the descriptors “transgender persons”, “gender identity”, “nursing care” and “primary health care”. Results. Eleven articles published between 2008-2021 were included. They were categorized as follows: Embracement and healthcare; Implementation of Public Health Policies; Weaknesses in academic training; Barriers between theory and practice. The articles showed a limited scenario of nursing care for the transgender population. The scarcity of research focused on this theme is an important sign of how care has been incipient or even non-existent in the context of PHC. Conclusion. Structural and interpersonal stigmas materialized in discriminatory and prejudiced practices perpetrated by managers, professionals and health institutions constitute the greatest challenges to be overcome for comprehensive, equitable and humanized care provided to the transgender population by nursing